The Dimension of Sincerity According To The Qur’an And Sunnah: The Key To Accepting Deeds - Rofi'i, Muhammad Arwani; Emilda, Puri; Rachmawati, Emilia (Institut Agama Islam Sumatera Barat, 2024)
This article aims to examine the dimension of sincerity (sincerity) in deeds according to the Qur'an and Sunnah, emphasizing the purity of intention, consistency in doing good, and independence from human praise. This study uses a qualitative method with textual analysis of relevant Qur'anic verses and hadiths. The findings show that sincerity encompasses relationships with both Allah and fellow humans, manifested through the concept of tawakkal (reliance on Allah) and fairness in social interactions. Sincerity in human relations creates an environment full of mutual understanding and compassion. In Islam, sincerity, derived from the Arabic word